Correlation study of tumor-infiltrating lymphocytes combined with residual cancer burden and prognosis in breast cancer patients receiving neoadjuvant chemotherapy - Hou, Zexin; An, Xueyuan; Meng, Guangmin; Zhao, Hongmei; Liao, Shanghua; Long, Xiaomin; Zou, Lingjun; Wu, Wen; Feng, Li; Liao, Guanghui (Frontiers in Oncology, 2025)
PurposeThis study investigates the feasibility of utilizing a combination of tumor-infiltrating lymphocytes (TILs) and residual cancer burden (RCB) to predict the prognosis of breast cancer (BC) individuals post-neoadjuvant chemotherapy (NAC).MethodsPatients with BC who underwent surgery following NAC were recruited from three medical centers for this research. RCB and TIL levels were determined using established guidelines, and the integration of RCB and TIL assessments was termed “RCB-TILs”. The relationship between RCB-TILs and patients’ clinicopathological variables was analyzed, alongside the link between RCB-TILs and disease-free survival (DFS).ResultsThe study comprised 242 BC patients who underwent NAC, among whom 98 were identified as RCB-TILs (+), while 144 were classified as RCB-TILs (-). Multivariate analysis demonstrated that RCB-TILs (+) served as an independent factor impacting recurrence following NAC across all BC patients (hazard ratio [HR] = 0.225, 95% confidence interval [CI]: 0.099 – 0.508, P < 0.001), including hormone receptor-positive patients (HR = 0.213, 95%CI: 0.067 – 0.682, P = 0.009), HER2-positive patients (HR = 0.216, 95%CI: 0.048 – 0.968, P = 0.045), and those with triple-negative BC (HR = 0.220, 95%CI: 0.049 – 0.989, P = 0.048).ConclusionsRCB-TILs (+) are correlated with extended DFS in BC patients who have undergone surgery post-NAC. In these individuals, RCB-TILs may provide a more sensitive predictor of DFS than RCB or TILs individually.